2021
DOI: 10.1111/dpr.12576
|View full text |Cite
|
Sign up to set email alerts
|

More evidence on the impact of government social protection in sub‐Saharan Africa: Ghana, Malawi, and Zimbabwe

Abstract: Motivation: Governments in sub-Saharan Africa have rapidly expanded cash transfer programmes as part of their social protection strategy over the last decade. Currently 46 countries have a state-sponsored social protection programme, compared to just 25 countries in 2005, and the most common type of programmes are cash transfers, representing 51% of all social protection spending in the region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 21 publications
(22 reference statements)
2
18
0
Order By: Relevance
“…Ethiopia's Productive Safety Net Programme is one of earlier major CT programmes in sub-Saharan Africa ( Garcia & Moore, 2012 ). Currently, 46 sub-Saharan Africa countries have state-sponsored social protection programmes ( Handa et al, 2021 ). The CCTs have been studied for their impacts related to health, education, nutrition, and food security in low- and middle-income counters.…”
Section: Related Literaturementioning
confidence: 99%
“…Ethiopia's Productive Safety Net Programme is one of earlier major CT programmes in sub-Saharan Africa ( Garcia & Moore, 2012 ). Currently, 46 sub-Saharan Africa countries have state-sponsored social protection programmes ( Handa et al, 2021 ). The CCTs have been studied for their impacts related to health, education, nutrition, and food security in low- and middle-income counters.…”
Section: Related Literaturementioning
confidence: 99%
“…It is estimated that around 20% of children eligible for anti-poverty social grants in South Africa do not access this support (23,24). Regional evidence supports the effectiveness of cash grants to address food security (25,26); and evidence from South Africa supports the potential of community initiatives to link eligible households to social grants (27). Therefore, in our analysis, we modelled the impact of a community outreach intervention implemented over 17 months during which paraprofessional social workers would actively liaise with community leaders and networks to screen for households that are eligible for the CSG in the community.…”
Section: Intervention 1: Outreach Intervention To Link Households Tha...mentioning
confidence: 99%
“…Estimates for intervention effectiveness were drawn from the academic literature, S3 Appendix. For community grant outreach, we generated a pooled estimate for the effect of cash transfers on food security by meta-analysis of two studies identified using a rigorous literature review, S4 Appendix (25,26). For parenting support, we used effect estimates for caregiver supervision taken from the original randomised evaluation of the PLH Teen intervention in South Africa (30).…”
Section: Intervention 3: Integrated Parenting Support Intervention Pl...mentioning
confidence: 99%
“…Well-being will be measured by the Cantril Scale [25], alcohol use will be measured by the Audit-C scale [26] which is scored on a scale of 0-12 (higher values represent worse outcomes), food insecurity will be measured by the Household Food Insecurity Access Scale [27], financial security will be measured by the Financial Security Scale [28], and stress level will be measured by Cohen's Perceived Stress Scale [29]. In addition to using the validated scales above, some questions in our questionnaire were adapted from the World Bank's Living Standards Measurement Survey [30], the Transfer Project's surveys [31], and the Kenya Demographic and Health Surveys [32].…”
Section: Data Collection Management and Safetymentioning
confidence: 99%